Efeitos imediatos da diafibrólise percutânea na avaliação da dor e estado funcional em pacientes com cervicalgia - Almeida, Arielem Lopes (ISB - Instituto de Saúde e Biotecnologia (Coari), 2022)
Introduction: The term neck pain refers to symptoms and/or manifestations of painful muscle changes in the cervical region. Percutaneous diafibrolysis is a non-invasive physical therapy technique used in the treatment of musculoskeletal conditions that trigger pain and/or movement restriction. Objective: This study aims to evaluate the effectiveness of percutaneous diafibrolysis by the parameters of pain intensity and functional status in individuals affected by neck pain. Methods: For this purpose, a randomized clinical study was carried out. The sample consisted of 71 volunteers, who were allocated into an experimental group (36) and a control group (35), and received treatment by percutaneous diafibrolysis and sham (simulated percutaneous diafibrolysis) respectively. The volunteers received a session of the technique and data were collected before and after this procedure regarding pain and functionality. Volunteers from both groups were evaluated using the NDI-BR questionnaire, Visual Analog Pain Scale - VAS, and Pain Pressure Threshold - by pressure algometry. Results: There was no difference in clinical outcome change and between types of treatment for variable pain intensity (VAS). Treatment by PD showed greater efficacy in relation to TS in the pain threshold variable measured by algometry. The group that received PD showed a significant increase in algometry after the intervention and presented a higher final result than the group that received the sham technique. For the NDI result, there was a statistically significant change between pre and post intervention. However, there was no difference between the different techniques used. Conclusion: Conclusion: With the present study, it was possible to elucidate through pressure algometry and NDI that the percutaneous diafibrolysis technique produces immediate effects in reducing pain (intra and between groups) and in improving cervical functionality (intra groups) even when performed a single session, being better than the simulated technique.